PENULISAN NASKAH DENGAN TEKNIK DESKRIPTIF DALAM PRODUKSI DOKUMENTER BIOGRAFI “PISAU BATIK MR. DIMAN” - Fanni Annisa Putri; Dwi Nurrahmi Kusumastuti; Imam Subechi (AKADEMI KOMUNIKASI RADYA BINATAMA, 2023)
ABSTRACT Biographical documentaries are documentaries that relate to stories someone's life. Biographical documentaries tell the story of a well-known person broad, has greatness, uniqueness, or other interesting aspects. On The documentary entitled